Formation of information support of financial control in the budgetary organizations - N. V. Borisova (Путеводитель предпринимателя)
In article the main directions ofinformation support of financial control of activity of budgetary organization of the health care which is carrying out rendering services in the field of health care for ensuring diverse needs of citizens on preservation of health, the prevention and treatment of various diseases reveal. Importance of introduction in these processes of information technologies promoting fast decision-making on the basis of the accelerated processing and providing information is emphasized.